2021
DOI: 10.1108/jfmm-08-2019-0167
|View full text |Cite
|
Sign up to set email alerts
|

E-store brand personality congruence for multichannel apparel retail brands

Abstract: PurposeThis study aims at examining the role of the e-store brand personality congruence/incongruence of a multichannel apparel retailer in the formation of consumers' perceived e-store brand fit and e-store patronage intention, based on the concept of image congruence.Design/methodology/approachAn online survey was conducted with a US national sample of 458 female consumers (20–50 years old) who had shopped for clothing online.FindingsResults revealed that e-store brand personality incongruence in three perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…The congruity‐premise also extends to matching digital BP with other constructs. For instance, Chang and Kwon (2022) argued for the importance of e‐store brand personality (in)congruence as an indicator of how well the BP of the e‐store reflected the personality of the overall brand (within‐brand‐congruity). Other researchers demonstrated that congruity between a brand's personality with its advertising context, the internet media's personality (Ham & Lee, 2015), or the fit between social media influencers, their followers, and brands have positive effects on consumer responses (Lee & Eastin, 2020; von Mettenheim & Wiedmann, 2021) (between‐brands‐congruity).…”
Section: Review Findings (Tccm)mentioning
confidence: 99%
“…The congruity‐premise also extends to matching digital BP with other constructs. For instance, Chang and Kwon (2022) argued for the importance of e‐store brand personality (in)congruence as an indicator of how well the BP of the e‐store reflected the personality of the overall brand (within‐brand‐congruity). Other researchers demonstrated that congruity between a brand's personality with its advertising context, the internet media's personality (Ham & Lee, 2015), or the fit between social media influencers, their followers, and brands have positive effects on consumer responses (Lee & Eastin, 2020; von Mettenheim & Wiedmann, 2021) (between‐brands‐congruity).…”
Section: Review Findings (Tccm)mentioning
confidence: 99%